Features of occlusal state in female Japanese patients with migraine: a case-controlled study. Issue 6 (1st November 2016) - Takeuchi, Mifumi; Saruta, Juri; Kato, Momoko; Sugimoto, Masahiro; Kamata, Yohei; Shimizu, Tomoko; To, Masahiro; Kawata, Toshitsugu; Igarashi, Hisaka; Tsukinoki, Keiichi
Abstract : Objectives: The prevalence rate of migraines is 8.4%; it is mostly diagnosed in women at 20s to 40s, and is known to cause major physical and mental disruption to daily life. This study was conducted on women aged between their 20s and 40s, in order to investigate the possible differences in the features of the occlusal state between a migraine and a non-migraine (control) group. Methods: Age-matched female patients with migraine ( n = 60) diagnosed by headache specialists and healthy controls ( n = 57) were enrolled. Dental casts were used to evaluate some features. Results: The maxillary and mandibular dentition casts from the migraine group showed significantly characteristic findings in their Angle's classification, overjet, and deviation in the anterior tooth midline, compared to the control group. Discussion: The results relating occlusal state to both tension-related headaches and migraines, which have different pathogeneses, suggest the possibility of dental intervention to improve the symptoms of primary headaches.